A nodule endophytic Bacillus megaterium strain isolated from Medicago polymorpha enhances growth, promotes nodulation by Ensifer medicae and alleviates salt stress in alfalfa plants. (19th February 2018) - Chinnaswamy, A.; Coba de la Peña, T.; Stoll, A.; de la Peña Rojo, D.; Bravo, J.; Rincón, A.; Lucas, M.M.; Pueyo, J.J.
Abstract: A Gram‐positive, fast‐growing, endophytic bacterium was isolated from root nodules of Medicago polymorpha and identified as Bacillus megaterium . The isolate, named NMp082, co‐inhabited nodules with the symbiotic rhizobium Ensifer medicae . B. megaterium NMp082 contained nifH and nodD genes that were 100% identical to those of Ensifer meliloti, an unusual event that suggested previous lateral gene transfer from a different rhizobial species. Despite the presence of nodulation and nitrogen fixation genes, the endophyte was not able to form effective nodules; however, it induced nodule‐like unorganised structures in alfalfa roots. Axenic inoculation promoted plant growth in M. polymorpha, Medicago lupulina, Medicago truncatula and Medicago sativa, and co‐inoculation with E. medicae enhanced growth and nodulation of Medicago spp. plants compared with inoculation with either bacterium alone. B. megaterium NMp082 also induced tolerance to salt stress in alfalfa and Arabidopsis plants. The ability to produce indole acetic acid (IAA) and the 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase activity displayed by the endophyte in vitro might explain the observed plant growth promotion and salt stress alleviation. The isolate was also highly tolerant to salt stress, water deficit and to the presence of different heavy metals. The newly characterised endophytic bacterium possessed specific characteristics that point at potential applications to sustain plant growth and nodulation under abiotic stress. Abstract : A Gram‐positive, fast‐growing, endophytic bacterium was isolated from root nodules of Medicago polymorpha and identified as Bacillus megaterium . Despite the presence of nodulation and nitrogen fixation genes, the endophyte was not able to form effective nodules, but it induced nodule‐like unorganized structures in alfalfa roots. The isolate was highly tolerant to salt stress, water deficit and heavy metals, and displayed plant growth‐promoting activities. Inoculation with the endophyte enhanced growth, promoted nodulation by Ensifer medicae and alleviated salt stress in alfalfa plants, pointing at potential applications to sustain plant growth and nodulation under abiotic stress.